2013
DOI: 10.5812/pedinfect.14202
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Childhood Asthma and Helicobacter pylori Infection in Sardinia

Abstract: Background: It has been suggested that Helicobacter pylori infection might reduce the risk of atopic conditions, such as asthma, in childhood. This risk reduction could relate to the "hygiene hypothesis" which proposes an association between childhood exposure to microbes and risk of atopy. Objectives: To examine the association between Hp infection and childhood acquired asthma in Sardinia. Patients and Methods:Children from Northern Sardinia who were between the ages of 10 months to 6 years and were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The results obtained in this study do not either confirm an inverse or a positive relation between atopic disorders, including asthma and H. pylori infection in children. These findings are consistent with our previous study conducted in the same geographic area [30]. In children aged 10 months to six years, screened for H. pylori infection using IgG serology and followed up for the occurrence of asthma and or allergic disease for seven years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results obtained in this study do not either confirm an inverse or a positive relation between atopic disorders, including asthma and H. pylori infection in children. These findings are consistent with our previous study conducted in the same geographic area [30]. In children aged 10 months to six years, screened for H. pylori infection using IgG serology and followed up for the occurrence of asthma and or allergic disease for seven years.…”
Section: Discussionsupporting
confidence: 91%
“…17.2% developed asthma, according to the Global Initiative on Asthma (GINA) [31], before the age of five years. Among them, 85.9% were H. pylori negative and 14.1% Hp positive [30]. By multiple logistic regression analysis H. pylori infection did not result significantly associated with childhood asthma.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another interesting example is co-infections of H. pylori and Salmonella typhimurium in mice (18). In another study, Maria PD et al did not find an association between H. pylori and pediatric asthma (19). Johan A et al found a significantly higher frequency of Giardia spp.…”
Section: Resultsmentioning
confidence: 99%
“…Among children aged 10 months–6 years screened for H. pylori infection using IgG serology and followed up for the occurrence of asthma and or allergic disease for 7 years, 17.2% developed asthma. Among them, 85.9% were H. pylori negative, and 14.1% H. pylori positive [32]. By multivariable regression analysis, H. pylori infection did not result significantly associated with childhood asthma.…”
Section: Discussionmentioning
confidence: 99%